PERANCANGAN TEKNIK DAN PROSEDUR PEMERIKSAAN PAJAK ATAS HARTA WAJIB PAJAK YANG MENGIKUTI PROGRAM PENGAMPUNAN PAJAK SESUAI UNDANG-UNDANG NOMOR 11 TAHUN 2016 - TINA MINIAWATI; ANDALA RAMA PUTRA BARUSMAN; SYAMSU RIZAL; DIKI CAHYADI (Universitas Bandar Lampung (UBL), 2018)
The research’s objectives are to design the tax audit techniques and procedures that can be used to carry out the tax audit on the asset tax payer who follow the tax amnesty program based on Law of The Republic of Indonesia Number 11 Year 2016 Concerning Tax Amnesty. The type of research is descriptive using qualitative approach. Based on the result, the writer found that tax treatment over additional assets and tax evasion practices will affect the three posts in the Annual Tax Return that is Earnings/income, income tax payable and depreciation/amortization expenses. Audit techniques that can be used is the use of internal/external information of Directorate General of Taxations, tracing, tracking evidence, testing the validity of document, confirmations, testing the truth of mathematical calculation, inspection and reviews. While the audit procedure is a series of steps that should be implemented to carry out a tax audit techniques.